2019
DOI: 10.1108/tr-05-2018-0060
|View full text |Cite
|
Sign up to set email alerts
|

Do tourists’ emotional experiences influence images and intentions in yoga tourism?

Abstract: Purpose The purpose of this study is to investigate the influence of tourists’ emotional experiences on predicting behavioral intentions via cognitive, affective and overall image in yoga tourism. Design/methodology/approach This study was conducted using data collected from 398 tourists visiting a yoga tourism destination in India. Confirmatory factor analysis and structural equation modeling were used in analyzing the collected data. Findings The study confirmed that specific tourists’ emotions act as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
7

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 78 publications
2
39
0
7
Order By: Relevance
“…Utilization feelings, for the most part, comprise different feelings and can be conceptualized as discrete feelings including interest, euphoria, misery, dread, scorn, disgrace, blame, appal, outrage and shock. These are clarified as positive and negative feelings (Sharma and Nayak, 2019). Jing and Rashid (2018) analyzed positive and negative consumption emotions and referenced in their study that travellers' emotional reactions are firmly connected with the post-consumption periods of experiences with the destination attribute performance.…”
Section: Variables For Destination Attributesmentioning
confidence: 99%
“…Utilization feelings, for the most part, comprise different feelings and can be conceptualized as discrete feelings including interest, euphoria, misery, dread, scorn, disgrace, blame, appal, outrage and shock. These are clarified as positive and negative feelings (Sharma and Nayak, 2019). Jing and Rashid (2018) analyzed positive and negative consumption emotions and referenced in their study that travellers' emotional reactions are firmly connected with the post-consumption periods of experiences with the destination attribute performance.…”
Section: Variables For Destination Attributesmentioning
confidence: 99%
“…For example, "yoga tourisma way for healthy living." This argument is supported by a study which found a connection between the emotional content of the advertisement and tourist's motivation and intention to visit a destination (Min et al, 2013;in Sharma & Nayak, 2018).…”
Section: Yoga Tourism As Wellness Tourismmentioning
confidence: 86%
“…brand/visitor community, family/friends, relationship to home and selfbrad integration) issues that influence destination attitude Williams et al (2019). From the experiential marketing perspective, a number of factors, including multisensory marketing, brand experiences and perceived value (Wiedmann et al, 2018) as well as image (Sharma and Nayak, 2019;Manyiwa et al, 2018) directly and/or indirectly enhance brand strength. As a way to change from negative to positive attitude toward destinations, the concept of consumer affinity has been emerged in marketing literature.…”
Section: Brand Equitymentioning
confidence: 99%